Augmented Reality and Pedagogical Anthropology: Reflections from the Philosophy of Education - Fuentes, Juan Luis (Augmented Reality: Reflections on Its Contribution to Knowledge Formation, 2023)
Philosophy of education, as applied philosophy, deals with educational issues from a philosophical point of view, including those raised by modern technology. Being a form of social interaction, education is probably one of the experiences most altered by technology; through ICTs, it has gained a myriad of options not only for accessing knowledge but also for human development. In this chapter, I will analyze some challenges that Augmented Reality presents in philosophy of education, paying particular attention to its ramifications for pedagogical anthropology. To be specific, I will explore the following human traits: lack of instincts and its influence on the development of initiative; human precariousness in the environment and ability to adapt; ontological knowledge of reality, through transmediation, and Zubiri’s concept of the human being as an “animal of realities;” and, finally, leisure understood as a non-vital human need. © 2017 Walter de Gruyter GmbH, Berlin/Boston.
Keywords: augmented reality; human initiative; human precariousness; leisure; ontological knowledge; pedagogical anthropology; philosophy of education; transmediation; Scopus(2)